Persoalan Pengembangan Institusi Pemberdayaan Masyarakat - Soetomo, - (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2006)
Transformation from production oriented development to people centered development requires a deeply rooted local institutions. The critical challenge to deal is how to manage the process of institutionalization